PEDAGOGICAL AND MOTIVATIONAL PRINCIPLES OF QUALITY ASSURANCE OF CHEMICAL EDUCATION IN TECHNICAL UNIVERSITIES OF UKRAINE: PROBLEMS, EXPERIENCE, PROSPECTS - Andrii Pidgornyy; Tetiana Duda (Izdevnieciba "Baltija Publishing", 2022)
The purpose of the paper is to consideration of the main motivating factors for ensuring high-quality education of engineers to achieve European standards of higher education based on the analysis of the educational process in the fundamental subject of Chemistry among engineering students at Igor Sikorsky Kyiv Polytechnic Institute over three years (2019, 2020, 2021). The article analyzes the principles of the educational process in the university, identifies the advantages and disadvantages of the modern system of engineering education, proposes motivational factors to improve the quality of education and identifies the main approaches to the formation and development of necessary professional competencies of graduates. Methodology. To achieve this goal, theoretical and empirical research methods were used: the method of critical analysis of pedagogical and methodological research papers on the issue; analysis of applicable laws of the Ministry of Education of Ukraine and regulations of the education process in the Igor Sikorsky Kyiv Polytechnic Institute; method of scientific observation of the educational process at the Departments were the authors teach subject "Chemistry" (namely, all of departments of the Institute of Mechanical Engineering: Department of Applied Mechanics, Department of Dynamics, Mechanical Engineering and Support Materials , Department of Machine Design, Department of Technology Machine Construction and some of departments of the Institute of Welding and Material Science: Department of Laser Technology, Department of High Temperature Materials and Powder Metallurgy, Department of Welding ). The total number of students who participated in the learning process, the number of attended lectures, consultations, laboratory and practical classes were counted. The percentage of students who successfully passed and passed the course (grade 60% out of 100%), the percentage of students who did not pass the course (grade 60% out of 100%), the percentage of students who regularly and independently completed individual assignments, the percentage of students involved in scientific work, and the ratio of students studying online and offline were determined. Questionnaires were also used for students in these departments regarding motivation to study, examination results, difficulties in learning, and communication with teachers. A total of more than 600 students were surveyed, each of whom gave six sets of answers (2 times for every three years) to the questionnaire. The aim of the article is to analyze the experience of modernization of basic chemical education for students of natural sciences, to identify the motivating factors for improving the quality of education at each level - individual, state, university - and to identify the difficulties and ways to overcome them. Conclusion. Successful engineering and special training in the system of higher technical education should be based on the scientific basis of the corpus of basic natural sciences. Given the relevance of chemistry in today's reality for the creation and implementation of innovative developments and technologies, the relevance of training in environmental and energy management, sustainable development, the relevance of strengthening the chemical component in the educational and professional training programs of bachelors of engineering is obvious.